Role of omega-3 polyunsaturated fatty acids, citrus pectin, and milk-derived exosomes on intestinal barrier integrity and immunity in animals - Tamil Selvi Sundaram; Carlotta Giromini; Raffaella Rebucci; Juraj Pistl; Mangesh Bhide; Antonella Baldi (Journal of Animal Science and Biotechnology, 2022)
Abstract The gastrointestinal tract of livestock and poultry is prone to challenge by feedborne antigens, pathogens, and other stress factors in the farm environment. Excessive physiological inflammation and oxidative stress that arises firstly disrupts the intestinal epithelial barrier followed by other components of the gastrointestinal tract. In the present review, the interrelationship between intestinal barrier inflammation and oxidative stress that contributes to the pathogenesis of inflammatory bowel disease was described. Further, the role of naturally existing immunomodulatory nutrients such as the omega-3 polyunsaturated fatty acids, citrus pectin, and milk-derived exosomes in preventing intestinal barrier inflammation was discussed. Based on the existing evidence, the possible molecular mechanism of these bioactive nutrients in the intestinal barrier was outlined for application in animal diets.